TACIS and EU's security of energy supply: the Commission as a strategic actor in external relations - Sebastian Mayer (Universität Bremen, Collaborative Research Center 597 - Transformations of the State, 2006)
This article seeks to explain why EC Members in 1990 delegated competences in the coordination of TACIS - a technical assistance programme with energy related aspects for the former Soviet Union - to the Commission, and to determine whether this institution succeeded in exerting an independent influence on the course of the EU's external energy policy in the following years. Four mechanisms will be used to explain the institutional independence: Path Dependence and Unintended Consequences; Formal and Informal Agenda Setting; and Fuzzy Legal Boundaries. It can be demonstrated that the Commission has considerably increased its competences in energy politics since the instigation of TACIS. The Commission has exploited institutional rules to take the initiative, redefined the energy sector in relation to foreign and security policy, and thereby has managed to shape EU's external energy policy over time. Ultimately, we can observe the establishment and subsequent interlocking of functions beyond the nation-state together with those still within governmental confines.
Keywords: 330